2010
DOI: 10.1007/s10029-010-0690-z
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral occurrence after laparoscopic total extraperitoneal hernia repair for unilateral inguinal hernia

Abstract: The incidence of contralateral occurrence after TEP was found to be low. TEP is a valuable procedure with a low contralateral occurrence rate, and repeated TEP for contralateral occurrence can be performed easily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Saggar and Sarangi3 found occult contralateral hernias in 8% of patients, but only 1% of these subsequently developed a symptomatic hernia during a follow-up period ranging from 10 to 82 months. The other report found that 5 of 157 (3.2%) patients with unilateral TEPs developed a hernia on the contralateral side after 1-year follow-up 11. Also, higher percentages of symptomatic hernia occurrence have been published.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Saggar and Sarangi3 found occult contralateral hernias in 8% of patients, but only 1% of these subsequently developed a symptomatic hernia during a follow-up period ranging from 10 to 82 months. The other report found that 5 of 157 (3.2%) patients with unilateral TEPs developed a hernia on the contralateral side after 1-year follow-up 11. Also, higher percentages of symptomatic hernia occurrence have been published.…”
Section: Discussionmentioning
confidence: 96%
“…The other report found that 5 of 157 (3.2%) patients with unilateral TEPs developed a hernia on the contralateral side after 1-year follow-up. 11 Also, higher percentages of symptomatic hernia occurrence have been published. During 88 months of followup, 21% of occult incipient hernias became symptomatic requiring repair.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the latest systematic review, the incidence of occult inguinal hernias diagnosed at the time of laparoscopic inguinal hernia repair was 14.6%, and contralateral exploration and repair of occult inguinal hernias during laparoscopic repair is not warranted because of a high complication rate and limited benefits. 17 The incidence of subsequent contralateral hernia repair after primary unilateral TEP repair is reported to be 3.2% within 6 years, 18 and 11.8% within 10 years. 19 Several large cohort studies showed that the incidence of contralateral inguinal hernia after primary unilateral hernia repair is 6 to 11% within 2.5 to 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…Preperitoneal dissection on the contralateral side during TEP repair might increase the risk of injury to the spermatic cord. 18,24 However, several studies suggested contralateral exploration using the TEP approach. This procedure does not require skeletonization of the cord structures to detect the presence of a hernia and is safe without an increased risk of complications.…”
Section: Discussionmentioning
confidence: 99%